2021
DOI: 10.1007/s13300-021-01054-6
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Type 2 Diabetes and the Value of Achieving Near Normoglycemia from the Patient Perspective

Abstract: Introduction: Type 2 diabetes (T2D) is extremely burdensome to people with T2D and associated with impaired health-related quality of life. This study explores the impact of T2D and potentially relevant outcomes for new therapies using a unique approach to in-depth qualitative interviews where people with T2D are asked to think about their future with T2D. Methods: A cross-sectional qualitative interview study among people with T2D from the USA and UK. Interviews explored their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…Utility elicitation interviews were carried out with members of the general public in each of three countries (representing Europe, North America, and Asia), as preferred by relevant HTA bodies [ 11 – 13 ]. This sample size of ≥ 100 participants is also broadly consistent with prior research in T2DM on utility elicitation [ 16 18 , 32 34 ], or patient preferences in general [ 35 , 36 ]. In addition, a moderated 1:1 interview method (with highly consistent electronic data collection) was used, which represents the gold standard for health state valuation [ 23 ].…”
Section: Discussionsupporting
confidence: 77%
“…Utility elicitation interviews were carried out with members of the general public in each of three countries (representing Europe, North America, and Asia), as preferred by relevant HTA bodies [ 11 – 13 ]. This sample size of ≥ 100 participants is also broadly consistent with prior research in T2DM on utility elicitation [ 16 18 , 32 34 ], or patient preferences in general [ 35 , 36 ]. In addition, a moderated 1:1 interview method (with highly consistent electronic data collection) was used, which represents the gold standard for health state valuation [ 23 ].…”
Section: Discussionsupporting
confidence: 77%
“…Prior research has demonstrated that improvements in HbA1c, and specifically reaching near normoglycemia, is both meaningful and important to people with T2D in the US and UK. 18,19 This study demonstrates that the properties of tirzepatide, a novel, weekly, GIP/GLP-1 RA for T2D are valuable to people with T2D living in the US and UK. The tirzepatide efficacy and safety profiles differ from those of other T2D treatments that are currently available.…”
mentioning
confidence: 79%
“…This result is not surprising given past research has demonstrated people with T2D in the US and UK place a great deal of importance on reaching near normoglycemia and associate this with a range of positive impacts. 18 , 19 Weight reduction also influenced preferences; however, this attribute was secondary to HbA1c reduction in both countries (US RAI: 18.3%; UK RAI: 17.3%). The RAI for delivery system was higher in the US (RAI: 20.9%) than in the UK (RAI: 9.2%), with patients in both countries preferring the single-use, pre-filled pen over the multi-use, dial-a-dose pen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Despite the breadth of available treatments, people with T2D struggle with glycemic management, with nearly half of those with T2D having an HbA1c value of 7.0% or higher, in addition to having a variety of unmet needs while experiencing a wide range of impacts. [4][5][6] Previous research has found that poor glycemic management among people with T2D is associated with feelings of self-blame, poor psychological well-being, and diabetes-related worries. 7,8 A recent qualitative concept elicitation study was conducted to understand and document what achieving near normoglycemia (HbA1c levels near 5.7% or those observed among individuals without T2D) would mean to people with T2D.…”
Section: Introductionmentioning
confidence: 99%